PEMBINGKAIAN MEDIA DALAM PEMBERITAAN HUKUM KEBIRI KOMPAS.COM DAN TRIBUNNEWS.COM - Riris Arianti; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Cases of sexual violence against children have always increased significantly every year. Then to overcome this increase, the government and the President made and passed a chemical castration law. The sentences were made to provide a deterrent effect for perpetrators of sexual violence. However, until now the castration law has actually reaped many pros and cons. Including in the news on Kompas.com and Tribunnews.com which intensively reported castration laws differently. This difference is what initiates the researcher to find out how the two media frame the law of castration and how the two media build the framing of the law. Researchers used social reality construction theory andanalysis framing Robert Entmanto analyze the data. This analytical tool helps researchers to help understand how media packages events by defining problems, estimating the source of problems, making moral decisions and emphasizing resolution. In this way it can be seen how the media Kompas.com and Tribunnews.com frame the same event in the news. The results of the analysis show that there are differences in the frames made by Kompas.com and Tribunnews.com. The Kompas.com frame does not support the law of castration using a legal perspective. Then there are two frames made by Tribunnews.com, namely supporting the law of castration using the victim's perspective and the second frame not supporting the law of castration by packaging news headlines that are different from the content of the news.